Asymmetric Thickness of Oblique Capitis Inferior and Cervical Kinesthesia in Patients With Unilateral Cervicogenic Headache - Chen, Yi-Ying; Chai, Huei-Ming; Wang, Chung-Li; Shau, Yio-Wha; Wang, Shwu-Fen (Journal of manipulative and physiological therapeutics, 2018)
The purpose of this study was to compare the thickness of the oblique cervical inferior (OCI) and the error of the head reposition test between the painful and nonpainful sides of patients with cervicogenic headache (CeH) and between the patients and the asymptomatic group. Thirteen patients (24.5 ± 4.8 years) and 14 asymptomatic participants (23.9 ± 2.7 years) were included. The head reposition test was recorded by a 3-dimensional motion analysis system. The thickness of the OCI was recorded by ultrasonography. The measured outcomes were compared between the painful and nonpainful sides and with the asymptomatic participants. The thickness of the OCI in the rest condition on the painful side (9.92 ± 2.31 mm) was smaller than that of the nonpainful side (10.56 ± 2.24 mm). The constant error of the head-to-target test toward the nonpainful side was smaller in the patients with CeH (-1.6 ± 4.3°) than in the asymptomatic group (3.3 ± 3.7°, P = 0.005). Asymmetric OCI and cervical proprioception were demonstrated in patients with CeH.